PRESERVATION OF THE OLD‐GROWTH RELIC BUSULUK PINE FOREST UNDER THE CONDITIONS OF OIL FIELD DEVELOPMENT - P. V. Velmovsky; A. A. Chibilyov (Юг России: экология, развитие, 2019)
Aim. In this paper, we set out to analyse the problem of preservation of old‐growth relic pine forests under in the context of oil field development.Discussion. The Buzuluk pine forest is the largest natural island forest in the steppe zone of European Russia. Presenting a landscape isolate of old‐growth natural pine and pine‐broadleaved forests, this unique natural object received the status of a national natural park in 2007. In this territory, former oil and gas fields are currently being prepared for operation and maintenance. The Buzuluk pine forest has been a subject of intense scientific interest due to a number of preserved standards of old‐ growth pine forests. These standards were originally identified and described by G.V. Morozov and V.N. Sukachev, thus forming a basis for modern forest biogeocenosis classifications. The paper discusses the current problems of the Buzuluk pine forest associated with the need to preserve old‐growth pine trees serving as standards. The consequences of oil production are assessed, with environmental restrictions in the zones of oil field exploitation being formulated. Industrial development of oil and gas fields inevitably leads to negative consequences, includ‐ ing the loss of ecosystem stability, a decrease in biological diversity and landscape degradation.Conclusion. The preservation of old‐growth pine trees is a necessary condition for the existence, restoration and sustainable development of the Buzuluk pine forest as a single ecosystem.